European mining and the social license to operate. Issue 2 (June 2021) - Lesser, Pamela; Gugerell, Katharina; Poelzer, Gregory; Hitch, Michael; Tost, Michael
Highlights: The overarching governance of the EU creates a unique context for SLO. In Europe, good legislation and an active government are necessary for SLO. The Scalar SLO Model integrates community-level and societal-level SLO. The Scalar SLO Model integrates drivers of the loss of SLO. Future SLO research should focus on the relationship between community and society. Abstract: The Social License to Operate (SLO) has become an established part of the natural resource development lexicon in North and South America as well as Australia. In Europe, the concept of the SLO in relation to mining is still in early maturation and acceptance possibly due to the very different worldview that exists in Europe. The European 'condition' can be characterized by a greater degree of trust in governance bodies and the role they play in prioritizing the best interests of the citizens they serve. The 'Scalar SLO Model' is inspired by Thomson and Boutilier's original conception and developed during the H2020 MIREU project to describe the SLO in Europe; however, its logic can be applied to any other jurisdiction globally. What distinguishes the Scalar SLO Model from other contributions to the literature is two-fold. First, the division between the Community and Societal drivers of the SLO reinforces the notion that the nature of the SLO within the Community dimension can manifest itself differently than within the broader Societal dimension where values may not be the same. The second distinguishing contribution introduces the attributes of loss of the SLO as represented by conflictual relationships in both dimensions.